Evaluation of the theoretical and clinical methods for reducing marginal leakage in resin-based composite restorative materials: A review - Mohammad Ali Keshvad; Tabassom Hooshmand (Tehran University of Medical Sciences, 2016)
Resin-based composite restorative materials  have a substantial share in dental treatments. Their esthetic has made them patients’ first choice as restorative materials. Marginal leakage is one of their problems which leads to recurrent caries and post-operative hypersensitivity. Our aim was to evaluate the theoretical and clinical methods that have been proposed in the dental literature. Around 50 articles from Pubmed, SCOPUS and google scholar were selected and categorized in 4 groups based on the selected keywords. All the studies discussed in this paper have emphasized that there is no way to eliminate the microleakage but it can be reduced by means of some approaches. On the other hand, due to the multifactorial nature and difference of oral environment and laboratory conditions, there isn’t any certain way to define precisely. It seems that there is an absolute need for more research in this field to make the relation of theoretical results and clinical findings possible.